Inflation and growth: the international evidence - THIRLWALL, A.P.; BARTON, C.A (PSL Quarterly Review, 2014)
The work takes a large sample of countries and looks at the international evidence of the relation between inflation and growth, taking real growth unadjusted for population change, and cross-classifying countries according to their level of development and rate of inflation. The authors relate the analysis directly to growth theory by examining the relation between inflation and two important determinants of growth: the investment ratio and the balance of payments situation. Three conclusions are arrived at based on the analysis. First, for countries with relatively high productivity there is a distinct positive association between inflation and growth. Second, countries with a mild inflation of prices of between 3 and 10 percent per annum invest a higher proportion of their gross national product than countries with price stability. Third, inflation in excess of 10 percent per annum is positively detrimental to growth, investment and the balance of payments. JEL: E31, F32, E22